This Being is a Guest House: Embracing Humility, Liberation & Strengths in Therapy with Sexual and Gender Diverse Muslims. Issue 7 (7th June 2021) - Vaughan, Michelle; Ergun, Gokce; Williams, Julie
ABSTRACT: The complexity of the lives of sexual and gender diverse Muslims within the United States calls for mental health providers to own our power and privilege. Embracing cultural humility in service of aligning ourselves with liberation psychology, we call for an intersectionally informed, strengths-based approach to empowering/affirming clients whose diverse religious experiences intersect with their experiences of marginalization as sexual and gender diverse (SGD) Muslims. Drawing on extant personal narratives around mental health and therapy of this population, the authors offer critical reflections, processes and opportunities for clinicians to take responsibility in honoring the diverse journeys and experiences of SGD Muslims in serving them in journeys of healing.